PENGARUH KECERDASAN INTELEKTUAL (IQ) DAN KECERDASAN SPIRITUAL (SQ) TERHADAP PERSEPSI MAHASISWA AKUNTANSI MENGENAI KEETISAN PRAKTEK EARNINGS MANAGEMENT - Rochmah, Noer; Prihatiningtyas, Yeney Widya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The purpose of this study is to obtain empirical evidence about the influence of intellectual intelligence and spiritual intelligence simultaneously and partially on the perception of accounting studentabout the ethic of earnings management practices. The study was performed at 6 campuses in the Malang, namely University of Brawijaya (UB), State University of Malang (UM), University of Muhammadiyah (UMM), State Islamic University of Maulana Malik Ibrahim (UIN Maliki), Islamic University of Malang (Unisma), and Merdeka University (Unmer). Research methods used in this study was descriptive and explanatory studies, supported by the survey method. Data collection was done by questionnaire. Further more data, obtained were analyzed with descriptive statistical methods and multiple linear regression.Results of this study show that: 1) intellectual intelligence and spiritual intelligence had simultaneous significant effect on the perception of accounting studentabout the ethic of earnings management practice, and 2) intellectual intelligence and spiritual intelligence had partial significant effect on the perception of accounting studentabout the ethic of earnings management practice. From this study it was found that the higher the IQ or SQ, earnings management is increasingly perceived as an unethical practice. In addition, it was found that the intellectual intelligence had dominant influence than spiritual intelligence onthe perception of accounting studentabout the ethic of earnings management practice.However, it does not mean that SQ is not necessary, because SQ is essential part of intelligence and it is important to be taught. SQ has partialyeffected on the perception of the ethics of earnings management practices. Keywords : intellectual intelligence, spiritual intelligence, ethical perception, earnings management.